Genetic divergence in popcorn lines detected by microsatellite - Thatiana Silva Dandolini; Carlos Alberto Scapim; Antônio Teixeira do Amaral Júnior; Claudete Aparecida Mangolin; Maria de Fátima Pires da Silva Machado; Andressa de Souza Mott; Ana Daniela Lopes (Crop Breeding and Applied Biotechnology, 2008)
The purpose of this study was to use microsatellite markers to evaluate the genetic divergence in 10 popcornlines. The number of alleles per locus ranged from 2 to 5. The proportion of polymorphic loci was highest (50%) in lineCuragua, while Zélia II was the most monomorphic (100%). The arithmetic complement of similarity of Roger and Tanimotofor the 10 lines indicated lower genetic similarity between the lines Zélia II and Avati Pichinga I and higher similarity betweenZélia I and Zélia II. The mean distance between groups was greatest between the group formed by lines IAC 112 I 112 IAC II,Avati Pichinga I, Avati Pichinga II and the group containing Yellow Pear Popcorn II. Strategies on how to use the heterosisbetween different lines in partial diallel crosses are indicated.